Exploring injury assessment using motion tracking technology and ergonomic tools in archery performance - Ji, Xiaoxu; Arzalluz, Irati; Gao, Xin; Al Tamimi, Zainab; Swierski, Ethan; Piovesan, Davide (Frontiers in Medical Engineering, 2024)
Archers face a notable annual risk of injury attributed to the repetitive strain exerted on their upper body muscles and joints. This groundbreaking study marks the first utilization of real-time motion tracking combined with ergonomic analysis in archery research, eliminating the need for extensive equipment setups and streamlining data collection. Thirteen participants were involved, undertaking four tasks with varying draw weights of bows and target positions. The precise recording of human movements revealed distinctive postures adopted by both genders across different tasks. Furthermore, an assessment of exposed spinal force and its correlation with anatomical variables was conducted, providing valuable insights into injury risks during archery performances.